Gobi Altai, Khangai and Khentii Mountains mapped by a mixed-method cartographic approach for comparative geophysical analysis - Lemenkova, Polina (Mongolian Geoscientist, 2021)
Geologic and geophysical mapping has been so far limited to the traditional single-method GIS-based mapping. A new approach combining integrated analysis of data on geology, gravity, topography and geomorphology is presented for regional characterization of the geophysical setting in Mongolia: the Gobi Altai Mountains, the Khangai Mountains and Khentii Mountains with surrounding areas. Nine new maps have been produced from the high-resolution datasets: GEBCO, gravity raster, USGS geological data and SRTM-90 DEM geomorphological grid. Methodology includes three tools for cartographic data visualization: i) Generic Mapping Tools (GMT), ii) R programming language (‘raster’ and ‘tmap’ libraries); iii) QGIS. The results demonstrated strong agreement between the estimated values in gravity and topography grids, distribution of geological units and provinces over the country and geomorphological landforms with respect to the mountain ranges: Altai, Khangai and Khentii Mountains. The highest values in the gravity anomalies correspond to the mountain ranges in the Altai Mountains and Khangai Mountains (<80 mGal); high values correspond to the Khentii Mountains (20–60 mGal). Contrariwise, the basins of the Uvs Nuur and Khyargas Nuur show negative values (<-80 mGal). The NE- to NNE-oriented faulting and rift basins are clearly visible in the geophysical grids and geologic maps. The geomorphometric analysis performed based on the SRTM-90 DEM using R scripting demonstrated (1) slope, (2) aspect, (3) hillshade and (4) elevation models of Mongolia supported by histograms of data distribution and frequency. The study contributed to the cartographic methods and regional geological studies of Mongolia.